Risk factors and prognosis of recurrent wheezing in Chinese young children: a prospective cohort study - Guo, Jing (Allergy Asthma Clin Immunol, 2019)
BACKGROUND: Nearly all the investigations into the risk factors for wheezing and asthma were conducted in developed countries with a high prevalence rate of asthma and allergy, but the studies in developing countries are limited. In this study, we aimed to investigate the risk factors for different wheezing phenotypes in Chinese young children and to explore the prognosis of recurrent wheezing. METHODS: This cohort study contained the recruitment stage and the follow-up stage conducted by phone questionnaire survey. According to the information collected at the follow-up for wheezing episodes and remission age, our cohort was divided into transient wheezing, persistent wheezing and late-onset wheezing. The wheezing symptoms and potential risk factors were compared between these three wheezing groups. RESULTS: From the initial 109 participants, 78.0% completed the follow-up survey. The frequency of current wheezing at followup was significantly reduced in all three groups compared to the recruitment stage (p < 0.01). We observe a trend that the rhinovirus (RV) and respiratory syncytial virus (RSV) infection rates were higher in the persistent wheezing group, and the overall infection rates appear to be the lowest in late-onset wheezing group at recruitment. At follow-up stage, the rates of rhinitis ever and current rhinitis were both higher in the persistent wheezing (63.0%, 50.0%) and late-onset wheezing groups (88.2%, 58.8%), compared to the transient wheezing group (14.3%, 14.3%). The incidence of current wheezing episodes increased cumulatively if the participant had concomitant risk factors of rhinitis ever, aeroallergens sensitization at recruitment, either alone or together with previous RV infection at the time of recruitment. CONCLUSION: While the incidence of wheezing declined overall with age, but in addition to transient wheezers, additional subsets of children manifest persistent wheeze or late onset wheeze, and moreover the risk factors for wheezing display phenotypic variability between these subgroups. Rhinitis ever and aeroallergens sensitization, either alone or together with previous RV infection, were the most significant predictors for persistent wheezing in children in an eastern environment, such as in China.